Patent Ductus Arteriosus Before and After Surgery - Bambang Madiyono; Ismet N. Oesman; Sudigdo Sastroasmoro; Sukman Tulus Putra; Eva Jeumpa Soelaiman; Kukuh Basuki Rachmad (Indonesian Pediatric Society, 1989)
Twenty five patients with patent ductus arteriosus, who had undergone surgical closure were studied retrospectively. Girls were more affected than boys; the sex ratio was 4 : I. Associated cardiac lesions were diagnosed in 3 patients, two with ventricular septal defect and one with congenital mitral stenosis. Congestive heart failure was diagnosed in 5 patients before surgery. Typical continuous murmur was heard in most cases (76%), while in the rest only systolic murmur was detected. Electrocardiographic left atrial enlargement, left ventricular hypertrophy and right ventricular hypertrophy were found in 8%, 48% and 40%, respectively.Cardiomegaly with increased pulmonary vascular markings was found in 60% of cases, while ratio of left atrial to aortic root diameter greater than 1.2 was detected in 60% of patients. The PDA could be directly visualized by echocardiography in 15 cases.Cardiac catheterization was performed in 17 cases, 47% with hyperkinetic pulmonary hypertension, 41% with high pulmonary flow without pulmonary hypertension and 12% with mild increased pulmonary flow. The pulmonary-systemic flow ratio (Qp/Qs) was more correlated to pulmonary vascular markings rather than to cardio-thoracic ratio. Division of the ductus was the procedure of choice, but in 16% of cases ductal ligation was performed because of technical reasons. Postoperative catch-up in both weight and height was observed more clearly in children operated at earlier age. Ejection systolic murmur was still detected in 2 patients, in whom hyperkinetic pulmonary hypertension existed prior to surgery. No cardiomegaly was found in patients followedup I year or more after surgery. The mortality was nil.